Consistency guarantees for recovery of service-oriented distributed processing. (1st January 2013) - Brzeziński, Jerzy; Danilecki, Arkadiusz; Kobusińska, Anna; Szychowiak, Michał
One of the key problems of building complex service-oriented distributed applications is reliability of the processing despite possible failures of interacting entities. Some attempts to solve this problem have been proposed, including interaction compensation, service replication or rollback-recovery, among others. Yet, only the last one promises to develop mechanisms allowing automatic restoration of a consistent processing state, fully masking the failure occurrence. Unfortunately, the notion of consistent state is ambiguous and has not been formalised in the context of the service-oriented architecture (SOA). In this paper we propose formal definitions of contract guarantees and demonstrate that they can be successfully used to flexibly define consistency models for recoverable SOA applications.